N-Chloroisonicotinamide-A New, Mild, Effective, Efficient and Less Expensive Oxidant for Organic Substrates - Priya, V.; Mathiyalagan, N. (Asian Journal of Chemistry, 2010)
A new N-halo compound, N-chloroisonicotinamide is prepared by the chlorination of isonicotinamide. The physical constant, the formal redox potential, elemental analysis and spectral characterization (IR and 1H NMR) confirm the presence of nitrogen-halogen bond. It is found to be a fairly stable and mild oxidant of low cost. The possibility of the compound acting as an effective source of positive halogen is well established. It is screened for antimicrobial activity against bacteria and fungi at various concentrations using disc diffusion method.